(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: The aim of the study was to evaluate the effect of Neo-Mineral Trioxide Aggregate and hydroxyapatite nanoparticles on the proliferation and osteogenic differentiation of apical papilla stem cells (SCAPs) Conclusion: Within the limitations of this in vitro study, it can be concluded that: Isolation of SCAP can be done from extracted fully impacted immature third molars. All tested biomaterials have the ability to induce osteogenic differentiation and proliferation of SCAP. Nano Neo MTA biomaterial has increased ability for differentiation of SCAP to osteoblasts. Nano NeoMTA biomaterial has increased ability for proliferation of SCAP proved by upregulated cell viability